Nghiên cứu chiết tách và làm giàu xeerri từ sa khoáng monazit - Hai, Phạm Văn (Vietnam Journal of Chemistry, 2014)
In this paper, a synergistic extraction effect that is based on the mixture of triizoamylphosphate (TiAP) and 2-ethylhexyl 2-ethylhexyl phosphonic acid (PC88A) using petroleum as diluent is applied to effectively extract and purify cerium from monazite mineral sand ore located in Nuithanh District, Quangnam Province. Rare earths in monazite are extracted and scrubbed from the organic phase with 6M HNO3. After that cerium is separated from the rare earths at the purify of 99.05% by the use of the reduction agent of 10% H2O2, and 2 stages of scrubbing with 6 M HNO3.